An air-to-ground combat survivability model. (July 2015) - Erlandsson, Tina; Niklasson, Lars
A survivability model can be a useful component of a tactical support system able to aid fighter pilots to assess the risk of getting hit by enemy fire from ground-based threats. This work identifies three desirable properties of such a model: it should allow for evaluating actions; it should enable domain experts to incorporate their knowledge; and it should represent uncertainties both regarding the locations of the threats as well as their future actions. A survivability model is suggested, which calculates the probability that the aircraft can fly a route unharmed and allows for routes of different lengths to be compared. A domain expert can describe the threats by specifying the risk of getting hit at a position of the route without having to consider the earlier actions of the aircraft and the threats. Three different threat models are suggested and compared. The influence of uncertainties regarding the positions of the threats is studied by calculating the probability density function for the survivability. Different representations that take into account both the uncertainty regarding the present and future situation are discussed. The results indicate that the suggested survivability model could be a useful component of a future tactical support system, even though some further development is needed.